Failure Investigation of Plastic Shredding Machine’s Flange Coupling Based on Mechanical Analysis - Ignatius Pulung Nurprasetio; Bentang Arief Budiman; Farid Triawan (Indonesian Journal of Science and Technology, 2017)
This paper presented the investigation of failure mechanism of plastic shredding machine’s flange coupling which is made of cast steel. The machine unexpectedly stalled a few minutes after High-Density Polyethylene (HDPE) plastic bottles were fed into the machine. It was discovered afterward that the flange broke with the large crack surface. Finite element analysis (FEA) was performed to find the position and value of the critical stresses in the flange during operating condition. Subsequently, hardness test was conducted on the flange body to determine the Brinell hardness which was then converted into the approximate ultimate tensile strength (σu). As a result, a maximum Von Mises stress of 287 MPa was confirmed from the FEA to be concentrated in the flange’s keyway. Although this was found to be lower than the approximate σu obtained from hardness testing i.e. 449 MPa, the critical stress indicated an unstable condition which may induce a crack initiation any time when vibration or dynamic load occurs. Based on these analyses, it was concluded that the failure had been initiated by dynamic rather than static loading generated during machine stall condition. The dynamic load caused crack initiation at a stress concentration point of the keyway. The crack then propagated rapidly, breaking the flange body.